Sex-related perception of body image, attitude toward food, and nutritional status of university students, and their relationship with physical activity level - Patricia Ruiz-Bravo; Sonia García-Merino; Bárbara Rodríguez-Rodríguez; Nuria Mendoza Laiz; Germán Díaz Ureña (Frontiers in Psychology)
University life is a critical period for acquiring and consolidating healthy habits. This study examined the influence of sex on the body image perception, attitude toward food, nutritional status, and lifestyle habits of university students. This descriptive observational study included 163 university students from a program of Health Sciences. The data were collected with digitally distributed, self-administered questionnaires. Instruments such as the International Physical Activity Questionnaire were used to measure physical activity, the Eating Attitudes Test-26 to assess attitudes toward food, the Multidimensional Body Self Relations Questionnaire and Gardner’s assessment for body image perception, and the Prevención con Dieta Mediterránea for adherence to the Mediterranean diet. Body composition was evaluated with an InBody 770 device. Most of the values found were within the appropriate range and not significant in practice, except in the Gardner test for women, where relevant values were found. Female participants demonstrated greater dissatisfaction with their body image and higher EAT-26 scores, indicating an increased risk for eating disorders. Male participants exhibited higher body mass index and physical activity levels. No significant differences were observed in adherence to the Mediterranean diet between the sexes. Correlations between the variables revealed that body dissatisfaction was associated with a higher percentage of body fat and visceral fat area in both sexes. Gender differences in body image perception and attitude toward food underscore the need for sex-specific interventions. Promoting a positive body image perception and healthy eating habits is essential for improving the physical and mental health of university students. Educational programs should consider these differences and emphasize the promotion of physical activity and adherence to balanced diets.